Biogas production from corn stalk as agricultural waste containing high cellulose material by anaerobic process. (2022) - Sumardiono, Siswo; Hawali Abdul Matin, Hashfi; Ivan Hartono, Ignatius; Choiruly, Luthfi; Budiyono,
Abstract: Many developing countries like Indonesia are experiencing serious problems associated with fossil energy reserves that has declined in line with population growth. To overcome these problems is necessary to renewable energy sources. Biomass-based renewable energy sources are a major contributor to renewable energy. Agricultural waste is biomass containing lignocellulose and can be converted into biogas. This study aims to determine the effect of pretreatment of corn stalks on the yield of raw biogas. The raw materials used were corn stalks. The corn stalks are treated by physical pretreatment with particle size reduction, biological pretreatment with the addition of EM-4 as much as 3% v/v, 5% v/v, 7% v/v total, and the addition of NaOH as chemical pretreatment as much as 0.25 N, 0.50 N, and 0.75 N. After that, the substrate of corn stalks and cow manure are mixed in the biodigester with ratio 1:1, each substrate 18 g of total solid mass. Micronutrients (urea) were added as much as 0.3 g, then neutral pH was adjusted using HCl. Fermentation is carried out at ambient temperature. The volume of biogas was measured every two days by water displacement method. The fermentation process is observed for 62 days. Best results are obtained from corn stalks 20 mesh with the addition of EM-4 7% v/v and, where a maximum daily biogas yield 19.86 L/kg on day 28 and the total biogas production reached 215.77 L/kg. In conclusion, combination of physical, biological and chemical pretreatment of corn stalks are proven to increase the yield of biogas.